A Spinal Coded System for Fading Channels: Dynamic Decoding and Puncturing Strategy - Zhang, Zixuan; Zhao, Ling; Bai, Jiaming (IEEE transactions on vehicular technology, 2025)
Fading channels are pivotal in mobile communication, introducing varying levels of distortion that greatly affect transmission performance. While rateless codes like Spinal codes offer enhanced spectral efficiency in time-varying channels, they encounter practical hurdles in fading environments, such as high decoding complexity and the inability to leverage frequency diversity in multi-carrier systems. To overcome these challenges, this paper presents an optimized decoding and puncturing scheme. By leveraging equalization results to estimate and classify distortion levels in received symbols, our scheme allows for targeted adjustments to the decoding tree structure. In instances of decoding failure, the scheme selectively includes varying lengths of auxiliary information in the feedback, assisting the sender in making puncturing decisions. Through extensive simulations, we demonstrate rate performance increase of 7%-42% and decoding complexity decrease of 23%-70% compared to existing algorithms in severe multi-path scenarios, thereby enhancing the reliability and applicability of Spinal codes in fading channels.